Creative Thinking in The Development of DHT11 Plug-and-Play Temperature Sensor System - Baskoro, Farid; Suprianto, Bambang; Anifah, Lilik; Putra Nurdiansyah, Aristyawan; Rohman, Miftahur (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2023)
The emergence of IEEE 1451 is proof that plug-and-play can solve compatibility problems experienced by a variety of different sensors when accessing communication. The plug-and-play system makes it easy for users to innovate, add, remove or replace sensors. The convenience offered by the plug-and-play system requires researchers to be able to think creatively from the aspect of flexibility to implement plug-and-play which is integrated with the DHT11 temperature sensor so that the sensor can be directly connected to the interface. This study shows a plug-and-play process developed by a scanning process to find connected PORTs without having to do configuration, showing a comparison of the DHT11 error value with a comparator that reaches 0.628% in temperature values and 0.428% in humidity values. This study also shows 120 monitoring data of temperature and humidity values for one month obtained from the interface that has been made